Phase I and II trial on infusional 5-fluorouracil and gefitinib in combination with preoperative radiotherapy in rectal cancer: 10-years median follow-up. (March 2018) - Gambacorta, Maria Antonietta; De Paoli, Antonino; Lupattelli, Marco; Chiloiro, Giuditta; Solazzo, Angela Pia; Barbaro, Brunella; Alfieri, Sergio; Vecchio, Fabio Maria; Lenkowicz, Jacopo; Navarria, Federico; Palazzari, Elisa; Bertola, Giulio; et al.
Highlights: We report the long-term results of addiction of gefitinib to preoperative chemoradiotherapy in locally advanced rectal cancer. We wanted to see if the hight rate of pCR, already shown in previous studies, influenced survival outcomes. The first promising results have not been confirmed by a significant improvement in outcomes. Abstract: Purpose: The aim of this study is to evaluate the long term survival of the addition of gefitinib to chemoradiotherapy (CRT) in locally advanced rectal cancer (LARC). Methods and materials: This previously published multicentre, open-label, phase I-II study, enrolled patients (pts) with LARC to receive CRT with concurrent 5-fluorouracil continuous intravenous infusion and a dose escalation of orally administered gefitinib, followed 6–8 weeks later by surgery. An intra-operative radiotherapy boost of 10 Gy was planned. Adjuvant chemotherapy was administrated in ypN1-2 pts. After a median f/u of >10 years, we analyzed Local Control (LC), Metastasis Free Survival (MFS), Disease Free Survival (DFS), Disease Specific Survival (DSS) and Overall Survival (OS). Predictive endpoints of clinical outcomes were tested by univariate and multivariate analysis. Variables analyzed included: age, gefitinib dose and interruptions, adjuvant CT, surgery type, ypT, ypN, and TRG grade. We have also analyzed late toxicity according to CTCAEv4. Results: Of the 41 initially enrolled pts, 39 were evaluable (27M, 12F). With a median f/u of 133 months, LC, MFS, DFS, OS and DSS at 5 years were 84%; 71%; 64%; 87% and 92%, respectively. The OS and DSS at 10 years were 61, 5% and 76%, respectively. Grade 3-4 late toxicity occurred in 38% of pts: sexual (28, 2%) and gastrointestinal toxicities (10, 2%). Conclusion: Long term outcomes and late toxicity were similar to previously reported series. The addition of gefitinib did not improve outcomes in LARC. Gefitinib is not recommended for rectal cancer patients who received 5-FU based preoperative CRT. Further studies may identify if gefitinib is beneficial in selected group of patients.